THE NEED OF INTERDISCIPLINARY PARTNERSHIP IN RECREATION AREA TO WORK WITH STREET YOUTH - Lisauskienė, Dovilė; Aleksienė, Vilmantė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Both Europe and Lithuania aim at involving youth into the activities, encouraging their activeness and participation in social life. The article analyzes the social work with street youth. The initiatives of social work in informal environments of a city streets by applying interactive methods, interfering with creative-artistic or sports leisure activities are discussed. The results of the research carried out highlighted the need of interdisciplinary partnership in recreation area to work with street youth.